Extracellular molecular signals shaping dendrite architecture during brain development - Hamad, Mohammad I. K.; Emerald, Bright Starling; Kumar, Kukkala K.; Ibrahim, Marwa F.; Ali, Bassam R.; Bataineh, Mo’ath F. (Frontiers in Cell and Developmental Biology, 2023)
Proper growth and branching of dendrites are crucial for adequate central nervous system (CNS) functioning. The neuronal dendritic geometry determines the mode and quality of information processing. Any defects in dendrite development will disrupt neuronal circuit formation, affecting brain function. Besides cell-intrinsic programmes, extrinsic factors regulate various aspects of dendritic development. Among these extrinsic factors are extracellular molecular signals which can shape the dendrite architecture during early development. This review will focus on extrinsic factors regulating dendritic growth during early neuronal development, including neurotransmitters, neurotrophins, extracellular matrix proteins, contact-mediated ligands, and secreted and diffusible cues. How these extracellular molecular signals contribute to dendritic growth has been investigated in developing nervous systems using different species, different areas within the CNS, and different neuronal types. The response of the dendritic tree to these extracellular molecular signals can result in growth promoting or growth limiting effects, and it depends on the receptor subtype, receptor quantity, receptor efficiency, the animal model used, the developmental time windows, and finally, the targeted signal cascade. This article reviews our current understanding of the role of various extracellular signals in the establishment of the architecture of the dendrites